COOPERATION FOR THE CHILDREN’S HEALTH (EDUCATION IN THE 21ST CENTURY, 2023)
The article addresses issues of enhancing effectiveness of the process of correcting ofmusculoskeletal disorders (MSD), in particular, children’s posture through pedagogical means andmethods of physical education used in joint actions of family members and coaches.51The analysis of literature sources shows that the problem raised requires finding of moreeffective ways for solving the touched issue, since the state of MSD of the younger generation inmany countries is not at the proper level. Armenian schoolchildren are no exception in this regard,since according to YSMU, diseases of the musculoskeletal system of children are among the firstin the number of functional disorders.One of the ways to effectively solve this problem is to combine joint efforts of anorthopaedist, parents of children with MSD and swimming coaches. To solve this problem, itbecame necessary to implement a number of measures aimed at improving the level of theoreticaland methodological readiness, skills of parents and coaches to correct posture disorders.For this purpose, as part of a pedagogical experiment, seminars on the correction of posturedisorders were held. Parents were presented with programs of physical therapy classes at home,and coaches were presented with sets of exercises for therapeutic swimming aimed at posturecorrection.The developed programs were tested in a six-month pedagogical experiment carried out bothat home and in the pool with 10 children aged 11-12 years with posture disorders. With 10children of a control group of the same age with similar MSD, only swimming sessions inaccordance with established practices were held, without taking into account the doctor's diagnosisand number of methodological recommendations reflected in the scientific and methodologicalliterature.Analysis of data at the end of the study did not reveal any postural disorders in children of theexperimental group, while in the control group only half of them did not have any correction ofpostural disorders.The obtained experimental results indicate the effectiveness of joint actions of parents andswimming coaches in correcting posture disorders. To implement such cooperation it is necessaryto conduct educational sessions with parents and swimming coaches aimed at correction of posturedisorders within the relevant organizations.
Keywords: health, orthopedist, posture disorders, therapeutic swimming, coach, physical therapy, parents.